2013
DOI: 10.1111/php.12113
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Feeding of Opuntia Humifusa Inhibits UVB Radiation‐Induced Carcinogenesis by Reducing Inflammation and Proliferation in Hairless Mouse Model

Abstract: It has been validated that ultraviolet B (UVB) irradiation induced both squamous and basal cell carcinomas, as a tumor initiator and promoter. Opuntia humifusa is a member of the Cactaceae family which has been demonstrated in our previous study to have a chemopreventive effect in 7, 12-dimethylbenz[a]anthracene and 12-O-tetradecanoylphorbol-13-acetate induced skin carcinogenesis models. Therefore, this study was designed to determine the protective effects of O. humifusa against photocarcinogenesis. O. humifu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 35 publications
0
16
0
1
Order By: Relevance
“…Previous studies have demonstrated that the expressions of proinflammatory enzymes (iNOS and COX-2) and cytokines (TNF-α and IL-6) are induced by UVB exposure (Afaq et al 2003b; JA Lee et al 2013; Sharma and Katiyar 2010). We examined the effect of BBE on UVB-induced expressions of epidermal iNOS, COX-2, and TNF-α protein.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that the expressions of proinflammatory enzymes (iNOS and COX-2) and cytokines (TNF-α and IL-6) are induced by UVB exposure (Afaq et al 2003b; JA Lee et al 2013; Sharma and Katiyar 2010). We examined the effect of BBE on UVB-induced expressions of epidermal iNOS, COX-2, and TNF-α protein.…”
Section: Resultsmentioning
confidence: 99%
“…More studies are needed to confirm the protective effects of Opuntia spp., testing those compounds in a more physiological way or for instance by oral route that will take into account the digestibility and bioavailability of such compounds. In this spirit, O. humifusa fruit lyophilized powder given in the pelleted diet was reported to be protective in two different animal models of skin carcinogenesis, together with a reduction of skin lipid peroxidation and skin inflammation [122, 123]. …”
Section: Biological and Medical Properties Of Opuntia Spp In Chromentioning
confidence: 99%
“…Recently, it has been shown to have antifungal [23] and anticancer [24,25] properties, as well as to improve insulin sensitivity [26] and increase bone density [27]. The objective of this study was to analyze the possible anti-asthmatic effects of O. humifusa and their mechanisms.…”
Section: Introductionmentioning
confidence: 99%